Chemical composition of tourmalines from the Manjaka pegmatite and its exocontact, Sahatany Valley, Madagascar - Gadas,P.; Novak,M.; Vasinova Galiova,M.; Pezzotta,F. (Journal of Geosciences, 2023)
Chemical compositions and mineral assemblages of tourmalines from the elbaite-subtype Manjaka pegmatite in the Sahatany Valley, central Madagascar, and its exocontact were examined using EPMA and LA-ICP-MS. Several textural, compositional and paragenetic types of tourmalines were recognized in the individual pegmatite units and in the zones located towards the host rock in the order: wall pegmatite unit → border pegmatite unit → contact zone → recrystallization zone; the latter zone evidently originated after the host Mg-rich calc-silicate rock (Di + Tr + Qz > Pl + Kfs ˃ Phl + Dol ˃ Cal). Zoned prismatic crystals from the border unit evolved from the core Tur Ia (dravite < Fe-rich elbaite), Tur Ib (Mn,Fe-rich to Mn-rich fluor-elbaite > elbaite), to the crystal rims Tur II (elbaite > darrellhenryite) via the substitutions: (1) 2YR2+ = YLiAl, (2) YMnWF = YFe2+WOH, (3) YLi0.5WOH = YAl0.5WO, and (4) YLiTAlWOH3 = YAlTSiWO3. The contact zone, ˜2 mm thick, contains abundant Tur IV (Li,Fe,Al-enriched dravite > oxy-dravite), and the recrystallization zone, ˜1.5 cm thick, common Tur V (fluor-uvite > dravite > fluor-dravite, magnesio-lucchesiite, uvite) via the substitutions: (1) 2YR2+ = YLiAl and (5) YR2+WOH = YAlWO, (6) XNaWOH = XCaWO and (7) XNaYAl = XCaYR2+. The chemical compositions of the individual types of tourmalines suggest that the mobility of elements between calc-silicate rock and pegmatite was low. Only weak influx of Mg, V and Cr into pegmatite and Li and Al from the pegmatite to the host rock - recrystallization zone, respectively, were observed. The existence of thin B-rich contact zone with dominant Tur IV suggests low influx of B into the host rock in early magmatic stage. High contents of F in Tur V from the recrystallization zone were very likely triggered by influx of B,F-enriched residual pegmatite fluids. Very high a(B2O3), but low a(H2O) and a(F) in the pegmatite melt constrained very low degree of external contamination of the pegmatite. Compositional evolution in tourmalines from Manjaka was compared with the pegmatites and their exocontact at Stoffhütte, Koralpe, Austria, and Blizna I, Moldanubian Zone, Czech Republic.
Keywords: Tourmaline; granitic pegmatite; exocontact; mobility of elements; Manjaka; Madagascar